Proceedings of the first symposium on geomorphology and quaternary (Geology, Chulalongkorn, 1983)
This book deals with various interesting aspects of the histories of geomorphology and Quaternary geology in different parts of the world. The papers cover a range of topics: the origin of the term 'Quaternary', histories of ideas and debates relating to aspects of fluvial geomorphology, glacial geomorphology and glaciation, desert dunes and the geology of Thailand